INTERACTION BETWEEN ENVIRONMENTAL FORENSIC EXPERT WITNESS AND COURT DURING CRIMINAL PROCEEDINGS - E. Mayorova; N. Goncharuk; E. Adamova (Теория и практика судебной экспертизы)
The paper addresses the aspects of interaction between forensic witness experts and courts in the appointment and production of environmental forensic examinations during criminal proceedings. Some cases investigated by the RFCFS Laboratory of Environmental Forensics are offered as examples.